Choice with Endogenous Categorization. (10th March 2021) - Ellis, Andrew; Masatlioglu, Yusufcan
Abstract: We propose and axiomatize the categorical thinking model (CTM) in which the framing of the decision problem affects how agents categorize alternatives, that in turn affects their evaluation of it. Prominent models of salience, status quo bias, loss-aversion, inequality aversion, and present bias all fit under the umbrella of CTM. This suggests categorization is an underlying mechanism of key departures from the neoclassical model of choice. We specialize CTM to provide a behavioural foundation for the salient thinking model of Bordalo et al . (2013, Journal of Political Economy, 121, 803–843) that highlights its strong predictions and distinctions from other models.